Rh-endostatin Concomitant with Chemotherapy Versus Single Agent Chemotherapy for Treating Soft Tissue and Bone Sarcomas: A Systematic Review and Meta-Analysis - Zhuo Ma; Lifang Guo; Xiangli Cui; He Liu; Lihong Liu (Frontiers Media S.A., 2018)
Objectives: Endostar (recombinant human endostatin (rh-endostatin)), a 20-kDa proteolytic fragment of collagen XVIII, was approved for the treatment of non-small cell lung cancer (NSCLC). Recently, several studies have evaluated the efficacy of rh-endostatin combined with chemotherapy in the treatment of bone and soft tissue sarcomas. Here, we conducted a systematic review and meta-analysis to assess available evidence. Methods: Pubmed, Embase, Web of Sciences, the Cochrane Library and two Chinese literature databases (CNKI, WanFang) were systematically searched till May 20, 2018. Randomized controlled trials (RCTs) and cohort studies which compared the outcomes of rh-endostatin combined with chemotherapy versus chemotherapy alone for treating bone sarcomas or soft tissue sarcomas were included. The primary outcome was overall survival rate (OSR). Secondary outcomes included objectiveremissionrate(ORR), clinical benefit rate (CBR), disease control rate (DCR), distant metastasis rate (DMR) and adverse effects (AEs). The methodological quality of the included studies was evaluated. Data analysis was performed by Revman 5.3 software. Results: 9 studies comprising 839 patients were included. The pooled results indicated that, compared with chemotherapeutic agents alone, rh-endostatin combined group had a significant benefit in 1-year and 2-year OSR. However, there were no difference between 5-year OSR. OR, CBR and DMR were higher in rh-endostatin combined group. No significant difference was observed in the incidence of AEs. Conclusions: Rh-endostatin combined chemotherapeutic agents significantly improved clinical efficacy compared with chemotherapeutic agents alone in treating bone and soft tissue sarcomas. Moreover, combination of rh-endostatin with chemotherapy didn't increase the incidence of AEs. But more high quality RCTs with  large  sample  size  should  be  done  in  the  future  to confirm the conclusion.